Pengayaan Pengetahuan Lokal, Pembangunan Pranata Sosial: Pengelolaan Sumberdaya Alam dalam Kemitraan - Yunita T. Winarto; Ezra M. Choesin (Antropologi Indonesia, 2001)
For three decades, the management of natural resources has been oriented towards increased production and profit in the national economy or for certain stakeholders, sacrificing conservation and the prosperity of local people. The unavoidable results are the deterioration of natural resources, ecological pollution, and a decline in the people's ways and standards of living. This paper attempts to show that the sustainable management of natural resources can only be achieved if the state surrenders its domination and delegate rights to the local people as active actors. Besides the stories of how rich local knowledge, are some studies point out that local people have limited knowledge of the ecosystem, which carries the implication of weaknesses in natural resource management. Other cases focus on how the social institution (rules, conventions and control mechanisms) needed to overcome the problems of resource management has not been internalized, or has either been marginalized, or substituted by ineffective government institutions. The cases of rice farmers in Lampung and fish farmers in South Sulawesi as illustrated in this paper will show that special attention should be given to the enrichment of local knowledge, along with the creation, establishment and development of social institutions. For the sustainable management of natural resources in this country, it is important to consider the local people's rights of managing resources on their own, and the need for facilitation on the basis of partnership.